Oil under troubled water : Australia's Timor Sea intrique - Collaery, Bernard, 1944- (Melbourne University Press, 2020)
In May 2018 Bernard Collaery, a former Attorney-General of the Australian Capital Territory and long-term legal counsel to the government of East Timor, was charged by the Australian Commonwealth Director of Public Prosecutions with conspiracy to breach the Intelligence Services Act 2001. He was forbidden from talking about the charges against him, but under parliamentary privilege independent MP Andrew Wilkie revealed what has since been described as 'Australian politics' biggest scandal'. Five years earlier, after ASIO officers raided Collaery's home and office, Collaery told journalists that ASIS had been bugging the East Timorese government during negotiations over Timor Sea oil. He was about to represent East Timor; as well as calling the evidence of a former senior ASIS agent known publicly only as Witness K, at The Hague in a case against the Australian government. Oil Under Troubled Water relates the sordid history of Australian government dealings with East Timor, and how the actions of both major political parties have enriched Australia and its corporate allies at the expense of its tiny neighbour and wartime ally, one of the poorest nations in the world.